Hubungan antara Prostatitis Kronis dan Gangguan Reproduksi Pria: Tinjauan Literatur Terkini - Surya Putra, Abdul Hafiidh; Suryoadji, Kemal Akbar; Achmadsyah, Armand; Birowo, Ponco (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2025)
Background: This literature review aims to present the latest scientific findings that explain the relationship between chronic prostatitis and male reproductive disorders. Method: This study was a narrative literature review that identified articles from PubMed, Scopus, and Google Scholar using the keywords